An interface of Chlamydia testing by community family planning clinics and referral to hospital genitourinary medicine clinics. Issue 4 (1st October 2000) - Wilkinson, Chris; Massil, Helen; Evans, Jacqueline
Abstract : Objectives: To assess compliance with the protocol for the management of women with Chlamydia trachomatis diagnosed in community family planning (FP) clinics; to assess the rate of attendance at genitourinary medicine (GUM) clinics by these women; to assess the rate of adequate treatment and to assess the level of communication between GUM clinics and FP clinics. Method: Retrospective review of FP clinic records and case notes to identify all women with positive or equivocal Chlamydia results during a 6 month period, and a retrospective review of records from five local GUM clinics. Results: One hundred and twelve women were identified from FP clinic records with positive or equivocal Chlamydia results. Eighty-nine (79.5%) were referred to a GUM clinic. Twelve out of 14 women not referred had equivocal results. The median delay from the test being taken to the results being seen by a doctor was 9 days, and to the woman being referred was 10 days. Fifty-eight (51.7%, n = l12) women definitely attended a local GUM clinic. The FP clinics provided a letter of referral in 76 (85.4%, n = 89) women and the GUM clinics provided a letter of reply in 21 (48.8%, n = 43) women who attended with a referral letter. Three months after testing, only 54 (48.2%) of the 112 women with positive or equivocal Chlamydia tests were known by the referring FP clinic to have been treated. Conclusions: The majority of women with positive or equivocal Chlamydia results were referred to a GUM clinic according to the protocol. Attendance at GUM clinics was disappointing, as only 51.7% of the 112 women with positive or equivocal results had documented evidence of having attended. This raises the question not whether community clinics should be testing, but whether they should be initiating treatment and partner notification. Collaborative work between GUM clinics and community clinics around partner notification is needed, as well as funding for training and additional pharmacy costs. Further collaborative work between GUM and FP and reproductive healthcare (RHC) to evaluate the role of community clinics in the diagnosis and management of chlamydial infection and other sexually transmitted infections (STIs) is needed.